Comprehensive Physiology 2019
DOI: 10.1002/cphy.c180014
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystokinin (CCK) Regulation of Pancreatic Acinar Cells: Physiological Actions and Signal Transduction Mechanisms

Abstract: Pancreatic acinar cells synthesize and secrete about 20 digestive enzymes and ancillary proteins with the processes that match the supply of these enzymes to their need in digestion being regulated by a number of hormones (CCK, secretin and insulin), neurotransmitters (acetylcholine and VIP) and growth factors (EGF and IGF). Of these regulators, one of the most important and best studied is the gastrointestinal hormone, cholecystokinin (CCK). Furthermore, the acinar cell has become a model for seven transmembr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 360 publications
1
24
0
Order By: Relevance
“…A number of intracellular pathways have been activated following Nox1-derived ROS, including JNK, p38 MAP kinase, AKT, and ERK1/2 [44]. The same pathways are activated by CCK [45]. We found that caerulein-induced CP caused phosphorylation of AKT and decreased phosphorylation of JNK in WT mice.…”
Section: Nox1 Induces Phosphorylation Of Akt In a Mouse Model Of Cpmentioning
confidence: 61%
“…A number of intracellular pathways have been activated following Nox1-derived ROS, including JNK, p38 MAP kinase, AKT, and ERK1/2 [44]. The same pathways are activated by CCK [45]. We found that caerulein-induced CP caused phosphorylation of AKT and decreased phosphorylation of JNK in WT mice.…”
Section: Nox1 Induces Phosphorylation Of Akt In a Mouse Model Of Cpmentioning
confidence: 61%
“…CCK-8 and CCK-58 have the same effect on Ca 2+ signaling, zymogen activation, and cell death in PACs at high and low agonist concentrations in vitro (Criddle et al, 2009). A recent review has summarized the regulation of the CCK pathway in PACs in detail (Williams, 2019).…”
Section: Caerulein/cholecystokininmentioning
confidence: 99%
“…Subsequent studies carried out in animal models that simulate the human disease suggested that the PACs were the initial site of morphological damage (Lerch et al, 1992). The latest reviews summarizes the effects of CCK on PACs (Williams, 2019) and early acinar events in the pathogenesis of AP (Saluja et al, 2019). The most notable limitation of primary PACs is their in vitro viability is relatively short and thus they cannot be used for long-term experiments or subculturing, an advantage that acinar carcinoma cell lines can offer.…”
Section: In Vitro and Ex Vivo Modelsmentioning
confidence: 99%
“…Owing to the wide distribution and participation in important physiological functions, CCK1R and coupled signaling pathways are rather well characterized [27], including coupling to calcium signaling [1,2,28]. In contrast to reversible activation by agonists, one strikingly conspicuous feature of CCK1 receptor pharmacology is that CCK1R such as those present at the basal plasma membrane in rat pancreatic acini are permanently activated by the lowest lying excited state of molecular oxygen, the delta singlet oxygen ( 1 O 2 ) [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%